[PP.01.07] EFFECTS OF AZILSARTAN MEDOXOMIL ON CENTRAL AORTIC AND AMBULATORY BLOOD PRESSURE IN PATIENTS WITH MILD TO MODERATE ESSENTIAL HYPERTENSION. (September 2016) - Dobrokhod, A.; Sirenko, Y.; Zhyvilo, I.; Torbas, O.; Kushnir, S.; Granich, V.; Primac, G.; Polishchuk, S.; Sidorenko, P.; Rekovets, O.
Abstract : Objective: This study was planned to assess influence of azilsartan medoxomil (AZL) on central aortic blood pressure (CAP) and 24-hours blood pressure (BP) in patients with mild to moderate hypertension. Figure. No caption available. Design and method: Twenty-one patients (75% men, all white, mean age – 40 years) with mild to moderate essential hypertension, never treated before, were enrolled. Dose of AZL was gradually increased until maximum 80 mg once-daily. Follow-up of the study amounted to 6 months. CAP measurement (SphygmoCor CVMS, Atcor, Australia) and 24-hours blood pressure monitoring (ABPM, Meditech, Hungary) were measured before treatment and on the last visit. Results: Mean value (mean ± SEM) of baseline 24-hours systolic BP (SBP) was 141 ± 1.9 mmHg and 24-hours diastolic BP (DBP) – 84 ± 1.8 mmHg, while mean value of CAP was 136 ± 3.1 mmHg. At the end of the study mean value of 24-hours SBP was 126.6 ± 1.2 mmHg, 24-hours DBP – 75 ± 1.8 mmHg and CAP was 119 ± 2.9 mmHg. So decrease from baseline to final CAP, 24-hours SBP and 24-hours DBP were -17, -14 and -9 mmHg respectively. An outcome of the study shows a significant reduction in both 24-hours SBP and DBP (p < 0.0001) and CAP changes (p < 0.005). Conclusions: Once-daily AZL effectively lowers CAP in adults with mild to moderate essential hypertension and has shown good antihypertensive efficacy according to 24-hours blood pressure monitoring as well.